The Strategic Role of Entrepreneurial Marketing in Small and Medium Enterprises: Array - Nwankwo, Cosmas; Kanyangale, MacDonald Isaac (Acta Universitatis Danubius. Œconomica, 2020)
Without proper adoption of entrepreneurial marketing (EM) as a business strategy, many small and medium enterprises (SMEs) in both developed and developing economy would fail to survive. The aim of this conceptual paper is to elaborate the strategic role of EM in SMEs. To achieve this, the complexity of EM as well as the aspects of entrepreneurial marketing (EM) are discussed. The paper assert that strategic roles of EM embrace eight dimensions which are cardinal for SMEs to adopt not only to ensure the long-term direction of the business, but also leverage resources and capability to sustain advantage over competitors.